Pruning in guava (Psidium guajava) and appraisal of consequent flowering phenology using modified BBCH scale - SINGH, V K; RAVISHANKAR, H; SINGH, ANURAG; SONI, MANOJ KUMAR (The Indian Journal of Agricultural Sciences, 2015)
The guava (Psidium guajava L.) shows well defined phenological stages during growth, flowering and fruiting stages depending upon climatic conditions which of course is amenable to manipulations through cultural interventions. The BBCH scale (Biologische Bundesantalt Bundessortenant and Chemiscle Industrie) is used for recording the data of the different phenological stages in coded form starting from bud development, vegetative stages, floral stages and ends in fruit maturity. Pruning is an important tool for increasing the production but it impacts the normal phenological stages by causing variation in the occurrence of principal and secondary stages. Therefore, the normal BBCH scale proves to be erroneous. In order to assess the quantum of variation on the normal phenology, an experiment was carried out in the guava cv. Lalit for collection of phenological data using the traditional nomenclature described by Fleckinger (1945) and to relate them to the BBCH general scale in pruned or unpruned trees. Significant variation in the principal growth stages was observed as a result of pruning during February, May and September. The duration between the pruning and the beginning bud sprout was from 11 to 15 days during different times of pruning. In contrast, the control unpruned tree showed bud emergence within 2-3 days. The flowering in February and September pruned trees ranged from 78 to 93 days from flower opening and took 153 and 150 days, respectively, for the fruit ripeness as compared to control (129-146 days). Interestingly, beginning of bud sprout occurred in 7 days in May pruning as compared to 3 days in control and the 50 % flowering was hastened and occurred in 43 days and fruit ripening took 136 days. Thus the normal BBCH scale proved to be erroneous in trees subjected to pruning. Phenology of guava according to the traditional Fleckinger Code and the aberrations in the BBCH General Scale resulting from pruning is described in this paper.